2007
DOI: 10.1161/strokeaha.107.482950
|View full text |Cite
|
Sign up to set email alerts
|

Early Arterial Study in the Prediction of Mortality After Acute Ischemic Stroke

Abstract: Background and Purpose-The purpose of this study was to evaluate the value of the initial arterial study as a predictor of 90-day mortality in patients with acute ischemic stroke. Methods-A total of 1220 unselected patients assessed during the first 24 hours after stroke onset were prospectively studied. Initial stroke severity was evaluated by the National Institutes of Health Stroke Scale and dichotomized in mild (National Institutes of Health Stroke Scale Յ7) and severe (National Institutes of Health Stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 39 publications
2
34
0
2
Order By: Relevance
“…Correspondence with authors of relevant papers yielded additional data for 12 of the previously published studies, 4,17,20,21,35,[47][48][49][50][51][52][53] plus 3 additional unpublished data sets (1 of which has since been accepted for publication), 54 giving a total of 27 studies included in the primary analysis (Figure 1). …”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondence with authors of relevant papers yielded additional data for 12 of the previously published studies, 4,17,20,21,35,[47][48][49][50][51][52][53] plus 3 additional unpublished data sets (1 of which has since been accepted for publication), 54 giving a total of 27 studies included in the primary analysis (Figure 1). …”
Section: Search Resultsmentioning
confidence: 99%
“…Some authors have reported improved survival and functional outcome associated with statin treatment, but these findings have not been consistently replicated. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][31][32][33][34][35][36] Interpretations can be difficult because of limited sample sizes in some reports and possible bias in statin allocation in other studies, particularly those in which statins were allocated in a nonrandomized fashion. Some authors have also reported worse outcomes in patients treated with the combination of acute statins and intravenous thrombolysis.…”
Section: Ní Chróinín Et Al Statin Therapy and Outcome After Ischemic mentioning
confidence: 99%
“…All consecutive patients with acute stroke (nϭ1119) were considered for the study. Patients were included in the BasicMar database (grant supported by the Ministerio de Sanidad y Consumo, Instituto de Salud Carlos III; FIS Number PI051737) 19 an ongoing prospective register of patients with AIS at our hospital. This is the only public hospital serving a population of 300 000 people in 3 districts of Barcelona city.…”
Section: Methodsmentioning
confidence: 99%
“…This methodology has demonstrated a good correlation between explorations and interobserver. 19 Treatment was decided in each case by a neurologist experienced in neurovascular diseases following international consensus. In all cases we started antiplatelet therapy in the acute phase with the exception of those patients with cardioembolic strokes, and in some selected patients with severe arterial disease (patients already pretreated with antiplatelet, crescendo TIA, or progressive stroke after antiplatelet treatment) in whom anticoagulation was initiated.…”
Section: Methodology Of Carementioning
confidence: 99%
“…This last subgroup belongs to Parent Artery Disease (PAD), with the same prognosis of patients with large artery disease. The relation between the occlusive pattern and the outcome has been demonstrated by several studies, and then it is possible to say that "severe arterial stenosis/occlusion in the early arterial study was highly related with 90-day mortality in an unselected series of patients with stroke" (Ois et al 2007). This is right non only for severe stroke but also for mild stroke, and it is not related to the imaging technique used.…”
Section: Occlusive Pattern Diagnosismentioning
confidence: 97%